실내 곰팡이에 대한 금속 나노입자의 항진균 특성 - 윤선화; 배귀남; 이병욱; 지준호 (한국실내환경학회, 2007)
Airborne bacteria, fungi, and viruses are known to have adverse effects on human health. Various antimicrobial agents have been used to prohibit the growth of microorganisms on the surfaces of air filter media. In this study, nano-sized silver and copper particles were tested for their antifungal effects on indoor fungi, Cladosporium cladosporioides and Aspergillus versicolor. The growth circle of the fungi was observed on a solid agar plate containing the two nanoparticles. The nanoparticle concentration ranged from 0 to 500 μg/mL. The size of fungal growth circle seemed to decrease with increasing nanoparticle concentration in agar plates, indicating that silver and copper nanoparticles have antifungal properties against C. cladosporioides and A. versicolor.